Overlap in the cortical representation of hand and forearm muscles as assessed by navigated TMS - Fang Jin; Sjoerd M. Bruijn; Andreas Daffertshofer (NeuroImage: Reports)
The representation of upper limb muscles in the motor cortex is not clear-cut. The motor cortex contains areas that, when stimulated, may activate different muscles simultaneously, hence they seem to overlap. We expected the cortical representations of synergistic muscle pairs to overlap more than those of non-synergistic muscles. To test this, we used navigated transcranial magnetic stimulation to probe eight hand and forearm muscles of twenty healthy participants. We transformed the cortical representations of muscles to a template MRI to allow for group analysis. We found that the amount of overlap in cortical representations differed significantly between within-hand and within-forearm muscle combinations. Most synergistic muscle pairs, both within the hand, within the forearm and between them, had a larger overlap than non-synergistic muscle pairs. Our study demonstrates the largely overlapping nature of cortical representations of upper limb muscles. It is noteworthy that the overlap is elevated in muscles that usually act in a synergistic manner.